A review of energy storage and its utilization in Integrated Energy Systems. Issue 1 (June 2020) - Ji, Wenjia; Zhang, Han; Ding, Fei; Wang, Jiale; Zhang, Rui; Guo, Su
Abstract: Energy storage system is the central facility in the Integrated Energy System. It plays a significant role in the stable operation of the system and the distribution of the renewable energy sources. This thesis is based on the overall consideration of diverse systems and make a review of the different working conditions, classification, constraint conditions, operational modes and so on in the energy storage system.